2020
DOI: 10.3390/met10091159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Flank Cams Manufactured by WEDM and Milling Processes

Abstract: Cam-follower mechanisms are usually employed in different machines, like combustion engines, sewing machines, machine tools, etc. In the present paper, the option to manufacture cams utilizing wire electrical discharge machining (WEDM) has been considered. For this, surface roughness and shape error of cam profiles manufactured by the processes of milling and wire electrical discharge machining (WEDM) are presented. The methodology used covers different stages: design, prototyping, manufacturing, and measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…It is well known that, in FFF processes, high surface roughness is obtained in lateral walls, which are perpendicular to the deposition plane of the layers [ 25 ]. Similar R a values up to 0.41 µm were previously reported in machined flank cams [ 9 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is well known that, in FFF processes, high surface roughness is obtained in lateral walls, which are perpendicular to the deposition plane of the layers [ 25 ]. Similar R a values up to 0.41 µm were previously reported in machined flank cams [ 9 ].…”
Section: Resultssupporting
confidence: 88%
“…In aluminium machined cams, Veera et al [ 37 ] reported Ra values around 1 µm, which are higher than those obtained in this work. For structural steel flank cams, lower Ra values below 0.3 µm were reported [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation